2007
DOI: 10.1161/strokeaha.107.486506
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor Nrf2 Protects the Brain From Damage Produced by Intracerebral Hemorrhage

Abstract: Background and Purpose-Intracerebral hemorrhage (ICH) remains a major medical problem for which there is no effective treatment. Oxidative and cytotoxic damage plays an important role in ICH pathogenesis and may represent a target for treatment of ICH. Recent studies have suggested that nuclear factor-erythroid 2-related factor 2 (Nrf2), a pleiotropic transcription factor, may play a key role in protecting cells from cytotoxic/oxidative damage. This study evaluated the role of Nrf2 in protecting the brain from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
206
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(216 citation statements)
references
References 50 publications
10
206
0
Order By: Relevance
“…For example, systemic administration of sulforaphane reduced LPS-induced inflammation in the brain (13). In an intracerebral hemorrhage model, sulforaphane reduced oxidative stress-induced brain damage by activating Nrf2 signaling (23). In this study, we found that sulforaphane has strong analgesic effects on SNT-induced pain hypersensitivity, suggesting additional therapeutic potential for this molecule in the treatment of neuropathic pain.…”
Section: Discussionsupporting
confidence: 49%
“…For example, systemic administration of sulforaphane reduced LPS-induced inflammation in the brain (13). In an intracerebral hemorrhage model, sulforaphane reduced oxidative stress-induced brain damage by activating Nrf2 signaling (23). In this study, we found that sulforaphane has strong analgesic effects on SNT-induced pain hypersensitivity, suggesting additional therapeutic potential for this molecule in the treatment of neuropathic pain.…”
Section: Discussionsupporting
confidence: 49%
“…The former is known as intracerebral haemorrhage (ICH) and the latter condition is known as subarachnoid haemorrhage (SAH) (Feigin et al 2005). Reports using ICH models have shown that Nrf2 subjected to both pre-treatment and post-treatment are significantly effective in expressing Nrf2-dependent cytoprotective proteins, which subsequently cause a reduction in oxidative burden to brain tissue and, thus, increase the recovery of neurological function (Zhao et al 2007). It has been reported that, using SAH rat models, the Nrf2-ARE pathway is activated in the cortex during an early stage of SAH.…”
Section: Ischaemia and Strokementioning
confidence: 99%
“…Moreover, overexpression of Nrf2 protects cells from Fas-induced apoptosis suggesting an important role of Nrf2 in anti-apoptotic pathways (Kotlo et al, 2003). Activation of the Nrf2/ARE pathway has been shown to be neuroprotective following several types of acute insults to the central nervous system (CNS), such as intracerebral hemorrhage (Wang et al, 2007;Zhao et al, 2007bZhao et al, , 2009, focal cerebral ischemia (Zhao et al, 2006) and traumatic brain injury (TBI) ( Jin et al, 2009;Yan et al, 2008;Zhao et al, 2007a). Collectively, these observations suggest that Nrf2/ARE signaling plays an important role in cellular survival by modulating both cellular antioxidant potential and apoptosis pathway.…”
Section: Figmentioning
confidence: 99%